2013
DOI: 10.15282/jmes.5.2013.18.0069
|View full text |Cite
|
Sign up to set email alerts
|

Transient Semi-Circular Lid-Driven Cavity Flow using Non- Uniform Structured Grid Method with Upwind Scheme

Abstract: In this article, two-dimensional lid-driven cavity flow in a semi-circular cavity is simulated using a non-uniform finite different method with structured grid. NavierStokes and continuity equations are simplified using a non-dimensional streamfunctionvorticity approach. A Reynolds number of 1000 is used and the vorticity and streamfunction contour plot is monitored with convergence criteria of 1x10 -7 set to both the vorticity and the streamfunction value. The result shows that the primary vortex moves from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The flow inside a square cavity has been widely used to demonstrate fluid flow using simple geometry. The flow structure in a one-sided lid-driven cavity problem has been reported by many researchers (Ghia, Ghia, & Shin, 1982;Idris, Ammar, Tuan Ya, & Amin, 2013;Idris, Irwan, & Ammar, 2012;Musa, Abdullah, Azwadi, & Zulkifli, 2011;Rosdzimin, Zuhairi, & Azwadi, 2010;Sidik & Attarzadeh, 2011). Later, research on different cavity geometries has been reported, such as a deep cavity (Patil, Lakshmisha, & Rogg, 2006), semi-circular cavity (Yang, Shi, Guo, & Sai, 2012), trapezoidal cavity (Zhang, Shi, & Chai, 2010) and triangular cavity (González, Ahmed, Kühnen, Kuhlmann, & Theofilis, 2011).…”
Section: Introductionmentioning
confidence: 80%
“…The flow inside a square cavity has been widely used to demonstrate fluid flow using simple geometry. The flow structure in a one-sided lid-driven cavity problem has been reported by many researchers (Ghia, Ghia, & Shin, 1982;Idris, Ammar, Tuan Ya, & Amin, 2013;Idris, Irwan, & Ammar, 2012;Musa, Abdullah, Azwadi, & Zulkifli, 2011;Rosdzimin, Zuhairi, & Azwadi, 2010;Sidik & Attarzadeh, 2011). Later, research on different cavity geometries has been reported, such as a deep cavity (Patil, Lakshmisha, & Rogg, 2006), semi-circular cavity (Yang, Shi, Guo, & Sai, 2012), trapezoidal cavity (Zhang, Shi, & Chai, 2010) and triangular cavity (González, Ahmed, Kühnen, Kuhlmann, & Theofilis, 2011).…”
Section: Introductionmentioning
confidence: 80%